ANALISIS STRATEGI PEMBELAJARAN PADA MATA KULIAH PERSPEKTIF GLOBAL BERDASARKAN PERSEPSI MAHASISWA PGSD SEMESTER IV KELAS D UNIVERSITAS NUSA CENDANA - Jati Lamauran Koten, Gaudensius; Devidce Mbolik, Margret; Efinda Saputri, Matilda; Djogo Sena, Nathalia; Banola, Serentin; Wonda, Hiwa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe learning strategies in the Global Perspective course based on the perceptions of fourth-semester PGSD (Primary School Teacher Education) students, Class D, at Universitas Nusa Cendana. A quantitative descriptive approach was employed, with data collected from 29 students using a closed questionnaire on a four-point Likert scale. The instrument covered six indicators: learning approach, teaching methods, instructional media, learning interaction, student engagement, and classroom management. All 24 items were declared valid (r > 0.367) and reliable (Cronbach's Alpha: 0.819–0.899). Descriptive statistics computed via SPSS show that all six indicators fall in the